FREQUENCY OF HEPATITIS B IN ASYMPTOMATIC PATIENTS OF DISTRICT HEADQUARTER HOSPITAL KOTLI, AZAD KASHMIR - Sarwar, Javed; Ahmad, Waseem; Saleem, Mohammad; Jamshed, Fareeda; Gul, Nasreen; Idrees, Muhammad (Journal of Ayub Medical College Abbottabad, 2010)
Background: Hepatitis B is prevalent throughout the world including Pakistan. A large proportion of patients suffering from Hepatitis B may be asymptomatic and can transmit the disease to healthy population. Objectives of this study were to estimate the frequency of Hepatitis B in asymptomatic adult population coming to District Headquarter Hospital Kotli, Azad Kashmir and to determine the risk factors associated with its transmission. Methods: This was a cross-sectional study extending from January to December 2008. Subjects were randomly selected from those who attended the medial OPD of DHQ Hospital Kotli, Azad Kashmir for non-Hepatitis related problems. Both males and females between the ages of 15-80 years were included in the study. Blood samples taken from selected subjects were analysed for Hepatitis B surface antigen (HBsAg) by Immunochromatographic kit methods (ICT). Hepatitis B positive samples were further confirmed by third generation ELIZA. The patients thus confirmed were interrogated for different risk factors associated with transmission of Hepatitis B. Results: A total of 9,564 patients were analysed. Out of them 4230 (44.22%) were males and 5334 (55.77%) were females. Overall 141 (1.47%) patients were positive for HBSAg, 71 (1.68%) males and 70 (1.31%) females. Patients between 21-30 years of age were most commonly effected (35.46%, n=50). Blood transfusion was the most common risk factor (24.82%, n=35) associated with Hepatitis B transmission followed by dental procedures (14.18%, n=20). Conclusion: Frequency of Hepatitis B in asymptomatic people in this study was quite high. Blood transfusions and dental procedures were the most common risk factors associated with the transmission of Hepatitis B. Keywords: Hepatitis B, HBsAg, asymptomatic carriers, risk factors